(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2018)
This research presents a robust cloud-based healthcare security framework that integrates Multi-Factor Authentication (MFA) and Secure Multi-Party Computation (SMPC) to safeguard sensitive patient data. The framework ensures data privacy, secure access control, and encryption for electronic health records (EHRs) stored in the cloud. The proposed system is evaluated based on authentication time, encryption/decryption performance, and computational overhead. Experimental results indicate that encryption time ranges from 0.5ms to 5.8ms as data size increases from 10 KB to 1 MB, with decryption following a similar pattern. Additionally, computational overhead increases by approximately 18% with each additional authentication factor, reinforcing security without significantly compromising efficiency. The integration of MFA ensures that unauthorized access is effectively minimized, while SMPC enhances privacy by enabling secure data computations without exposing sensitive information. This approach demonstrates a significant improvement in balancing security and system performance, making it a viable solution for real-time healthcare applications. Future enhancements may focus on optimizing encryption techniques and reducing computational complexity to further improve efficiency. This research contributes to the ongoing development of secure and scalable cloud-based healthcare solutions, offering a practical approach to addressing security challenges in modern healthcare data management.